STABILISASI TANAH LEMPUNG DENGAN BAHAN TAMBAH ABU SEKAM PADI DAN KAPUR PADA SUBGRADE PERKERASAN JALAN - Muhammad Rifqi Abdurrozak (TEKNISIA, 2017)
Clay is a soft soil type that has fine grained soil characteristics and clay soil is very easy to inflate and shrink (expansive) by changes in water content. This shrinkage factor can cause the pavement layer above to be cracked and wavy. Because the nature makes clay soil as a less stable soil. This study aims to determine the influence of California Bearing Ratio (CBR) with the addition of rice husk ash and lime to soil improvement. Clay is from Kebonharjo village, Samigaluh sub-district, Kulon Progo district. This research used CBR testing method in laboratory using 28 samples. Sample samples conducted CBR testing without immersion and immersion CBR. The sample consisted of native soil with stabilized soil with additional 3%, 5% and 7% rice husk ash and 4% lime to be variable. The result of this research can be concluded that the CBR of original unsoaked soil shows the value of 9.46% and the original soaked soil is 1.16%. Addition of 3% rice husk and Lime 4% gives a significant increase of CBR up to 212% from original soil conditions. The curing process is proven to provide an increase in the CBR value, and at curing for 7 days shows that CBR value will have a constant value. The addition of rice husk ash up to 7% proved to increase the CBR value compared to the value of CBR of original soil. From swelling test shows the higher percentage of rice husk ash material gives the smaller swelling potential from the original soil by 4.8% to 0.032% on addition of rice husk ash (7%) and lime (4%).